ANALISIS PENINGKATAN PEREKONOMIAN DAERAH MELALUI UMKM DALAM MENGELOLA PRODUK KEARIFAN LOKAL DI KOTA TERNATE PROVINSI MALUKU UTARA - Darsanto, Darsanto; Effendy, Khasan; Nuryanto, Nuryanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The Implementation of regional development in the autonomy era is in accordance with Law Number 23 RI of 2014 concerning Regional Government based on regional capacities and initiatives. Where there are several development problem faced. Especially in Ternate City, when viewed from the perspective of population welfare, the problem of poverty and unemployment are still considered quite high. Therefore, strategic efforts are needed to deal with the problem in question. This paper aims to, 1) Describe the government’s efforts improved the regional economy through micro, small, and medium enterprises in managing local wisdom products in Ternate City, North Maluku Province; 2) Describe the factors that influenced efforts improved the regional economy through micro, small, medium enterprises in managing local wisdom product. The approach of this study was qualitative and descriptive method. The theory used to analyzed the main focus was The of Manpower Creation by Mansour Fakih. To saw the factors that affect the productivity of micro, small and medium enterprises used the concept proposed by Wilantara and Susilawati. The data sources were primary data and secondary data. Data collection techniques were obtained through interviews, observation and documentation carried out in Ternate City by involving the government and micro, small and medium enterprises by selecting a number of samples based on the snowball method. The results of this study indicate that the efforts made by the Local Government of Ternate City to improve its economy through micro, small, medium enterprises based on local wisdom potentiality are considered quite effective, because able to encourage and maintain productivity of business actors. These efforts generally take the form of development, fostering and provision of business capital that are regulative, service, facilitative and evaluative roles. Although, there are several obstacles that are quite prominent and influential, including the lack of business capital, product marketing, inefficiency of bureaucratics services, low human resource capacity for technology and limited raw materials. Therefore, it is recomended that there be improvements in term of increating business capital, marketing creativity, supply of raw materials and increasing the latest technology-based education and training activities.